DIALEK BAHASA JAWA NGOKO DESA SITIMULYO KECAMATAN PUCAKWANGI DAN DESA DUKUHMULYO KECAMATAN JAKENAN KABUPATEN PATI - Jumamik Jumamik; Umi Hartati (CARAKA, 2014)
This study aims to identify the shape ngoko vocabulary and use of particle shape in Javanese dialect Sitimulyo village subdistrict and village Pucakwangi Dukuhmulyo District of Jakenan Pati. This research is descriptive qualitative. The type of this research is descriptive qualitative. Source of data in this research is utterance (oral) which transcribed into writing. The data of this study is the use of the Java language that contain ngoko variations in vocabulary and forms particles that are spoken by indigenous peoples who live in the District Pucakwangi Sitimulyo village and sub-district village  Jakenan  dukuhmulyo Pati. Methods of data collection in this study was conducted using  ably  involved  refer,  recording technique and record engineering. Analysis of the data using the unified method, this method beyond the means of determining the relevant language. Exposure method of data analysis results using informal methods. The results of this study are vocabulary ngoko form and shape of particles using the  Java  language dialect sentence in the District Pucakwangi Sitimulyo village and sub-district village Jakenan  dukuhmulyo  Pati. Forms of  Javanese dialect vocabulary ngoko Sitimulyo village and sub-district village Pucakwangi dukuhmulyo Jakenan Pati District of experiencing symptoms of phonetic sounds and  morphological variation when compared with standard Java language. Variations of the phonetic sounds of symptoms in the form of 1) Change the sound, 2) Removal of phonemes, 3) addition of phonemes. Symptoms include morphological  affixation form: prefiksasi, sufiksasi, konfiksasi. The use of particle  shape  in  Javanese  dialect Sitimulyo village subdistrict and village Pucakwangi dukuhmulyo Pati District of Jakenan namely: particle  softeners, complementary particles, particles priority.